Cytotoxic effects of the nickel release from the stainless steel brackets: An in vitro study - Ajith Rajasekharan Pillai; Anil Gangadharan; Jithin Gangadharan; Nallasamy Vijaya Kumar (Wolters Kluwer Medknow Publications, 2013)
Aims: The purpose of the study is to determine whether the nickel released from the stainless steel brackets have any cytotoxic effects on gingival fibroblast. Materials and Methods: Brackets are an important component of fixed orthodontics. Orthodontists are mainly concerned about the brands and various systems incorporated into the brackets. The manufactures claim bracket superiority without valid research. Since we are dealing with a biologic system factors like biocompatibility, cytotoxic potential should be taken into consideration before selecting an appliance to the patient. The cytotoxic activity of the media was investigated with MTT and comet assay. Results: The results of the study show that the amount of nickel leached is capable of bringing damage to the fibroblast. Conclusion: Our study concludes that nickel solution at minimal concentration of 1.18 μg could damage human gingival fibroblast and the nickel released from the different brands of the brackets are not uniform.